Social support and physical activity change in Latinas: Results from the Seamos Saludables trial - Marquez, Becky (J Racial Ethn Health Disparities, 2015)
OBJECTIVE: Family responsibilities and poor social support are barriers to physical activity among Latinas. This study evaluated the effects of a home- and print-based intervention on social support, moderating effects of familial ties on support and moderate-to-vigorous physical activity (MVPA), and mediating effects of support on MVPA. METHODS: Participants were randomized to receive through the mail either individually tailored physical activity intervention or general wellness print materials. Familial ties and social support were assessed by marital and child status and the social support for physical activity measure, respectively. MVPA was measured using the 7-day Physical Activity Recall Interview and accelerometer. Assessments were conducted at baseline, 6 months post-treatment, and 12 months follow-up. RESULTS: Participants (n=266; 40.6 ± 9.9 years old) were mostly immigrant and Spanish-speaking Latinas. The intervention group achieved greater increases in family and friend support compared to the wellness control group from baseline to post-treatment and follow-up (p<0.05). Intervention changes in support did not depend on marital or child status. The intervention also increased minutes per week of MVPA more than the wellness control (p<0.05) and the effect did not depend on marital or child status. There were significant indirect effects of treatment, indicating the intervention achieved greater increases in MVPA by increasing family (ab=5.21, SE=2.94, 95% CI=0.91–14.11) and friend (ab=6.83, SE=5.15, 95% CI=0.16–20.56) support. CONCLUSIONS: The intervention improved and sustained support from family and friends and MVPA irrespective of familial ties. Social support mediated increases in MVPA.